In vitro antioxidant and anti-cholinesterase activities of Rhizophora mucronata. (2nd January 2016) - Suganthy, N.; Pandima Devi, K.
Abstract: Context : Rhizophora mucronata Lam. (Rhizophoraceae), commonly known as Asiatic mangrove, has been used traditionally among Asian countries as folk medicine. Objective : This study investigates the cholinesterase inhibitory potential and antioxidant activities of R. mucronata. Materials and method : Rhizophora mucronata leaves were successively extracted using solvents of varying polarity and a dosage of 100–500 µg/ml were used for each assay. Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitory activities were assessed according to the method of Ellman. In vitro antioxidant activity was assessed using free radical scavenging, reducing power, and metal-chelating activity (duration – 3 months). Total phenolic and flavonoid content were quantified spectrophotometrically. Compound characterization was done using column chromatography, NMR, FTIR, and LC-MS analysis. Results : Methanolic leaf extract (500 µg/ml) exhibited the highest inhibitory activity against AChE (92.73 ± 0.54%) and BuChE (98.98 ± 0.17%), with an IC50 value of 59.31 ± 0.35 and 51.72 ± 0.33 µg/ml, respectively. Among the different solvent extracts, methanolic extract exhibited the highest antioxidant activity with an IC50 value of 47.39 ± 0.43, 401.45 ± 18.52, 80.23 ± 0.70, and 316.47 ± 3.56 µg/ml for DPPH, hydroxyl, nitric oxide radical, and hydrogen peroxide, respectively. Total polyphenolic and flavonoid contents in methanolic extract were observed to be 598.13 ± 1.85 µg of gallic acid equivalent and 48.85 ± 0.70 μg of rutin equivalent/mg of extract. Compound characterization illustrated (+)-catechin as the bioactive compound responsible for cholinesterase inhibitory and antioxidant activities. Conclusion : The presence of rich source of flavonoids, in particular catechin, might be responsible for its cholinesterase inhibitory and antioxidant activities.